Determination of optimum age for transplanting cashew (Anacardium occidentale) seedlings in Northern Ghana - Opoku-Ameyaw, K.; Amoah; F. M., Oppong; F. K. and Agene; V (Global Journal of Food and Agribusiness Management, 2018)
The effect of age on the survival and growth of transplanted cashew seedlings was studied in the savanna ecological zone of northern Ghana in three field experiments. The seedling ages studied varied between 1.5 and 4.5 months after sowing. Seedling age significantly affected the survival of cashew seedlings one year after transplanting in two experiments with seedlings of between 1.5 and 2 months old establishing better than the older seedlings ages. Neither the growth of seedlings nor the proportion of plants that flowered two years after transplanting was significantly affected by seedling age at transplanting. A recommendation on the optimum period for raising cashew seedlings for transplanting in northern Ghana is given.